Mewujudkan Perdamaian Di Era Media Versi KH. Maimun Zubair : (Analisis Ma’na-cum-Maghza Atas Pesan KH. Maimun Zubair Di Media Sosial) - Alwi HS, Muhammad (MADINAH, 2019)
This article aims to show the contribution of KH. Maimun Zubair in creating religious and state peace, through the messages he conveys. KH. Maimun Zubair is not only a role model for Muslims, but also for other religious communities, especially in Indonesia. Departure KH. Maimun Zubair left very many messages, both messages that were conveyed orally and which have been transmitted into quotations, both relating to pesantrenan, religion in general, and about the state. Therefore, this article will discuss the role of KH. Maimun Zubair through the last message KH. Maimun Zubair through Nusron Wahid, who will then be drawn to the peace discussion in the nation and state. In analyzing the message, this paper uses a descriptive-analytical method using the Ma'na-cum-Maghza analysis from Sahiron Syamsuddin, namely understanding the initial meaning (ma'na) based on the author or first recipient, and developing the understanding or significance (maghza ) for the KH. Maimun Zubair. The question to be answered in writing is how to understand ma'na-cum-maghza from the last two messages of KH. Maimun Zubair in a peaceful religion and state?